Improving Effective Coverage in Health : Do Financial Incentives Work? - de Walque, Damien; Kandpal, Eeshani; Wagstaff, Adam; Friedman, Jed; Neelsen, Sven; Piatti-Fünfkirchen, Moritz; Sautmann, Anja; Shapira, Gil; Van de Poel, Ellen (Washington, DC: World Bank, 2022)
In many low- and middle-income countries, health coverage has improved dramatically in the last two decades, but health outcomes have not. As such, effective coverage -- a measure of service delivery that meets a minimum standard of quality -- remains unacceptably low. This Policy Research Report examines one specific policy approach to improving effective coverage: financial incentives in the form of performance-based financing (PBF) or financial incentives to health workers on the front lines.